Barriers and Resources to Optimize Bone Health in Orthopaedic Education: Own the Bone (OTB). Issue 4 (October 2021) - Levitt, Eli B.; Patch, David A.; Ponce, Brent A.; Razi, Afshin E.; Kates, Stephen L.; Patt, Joshua C.
Abstract : Introduction: Osteoporosis is a critical public health issue with substantial morbidity and healthcare costs. Resident education on osteoporosis is not standardized. Little is known about the barriers to osteoporosis treatment and the usefulness of educational programming from the perspective of orthopaedic residency program directors (PDs). Methods: This study aims to evaluate the current state and perception of bone health education from the perspective of orthopaedic residency PDs. Therefore, a self-designed 29-question online survey was sent to 129 PDs in the United States to assess bone health education. The information, collected from August to October 2020, included program characteristics, participation in the American Orthopaedic Association's Own the Bone (AOA/OTB) program or any fracture liaison service (FLS) program, availability of faculty, potential barriers, and educational resources. Data collection was performed anonymously with a 47% response rate. Results: The results were compared between programs that used the AOA/OTB program (30%) or any FLS program (28%) (58% OTB or any FLS) vs. programs that did not have any program (42%). Subsequent subanalysis was performed comparing AOA/OTB vs. any FLS vs. no program. Programs that did not have any FLS were least likely to have a formal education syllabus (p = 0.01). When comparing clinical education of residents on bone health, 64% of programs without any system did not provide any formal clinical exposure such as a bone health clinic vs. assessment in patients with fracture compared with 24% of OTB programs and 44% of programs with any FLS (p = 0.02). When asked about desired resources, 47% would find a bone health rotation useful. Among all PDs, 60% support the concept of a 5-year AOA Council of Orthopaedic Residency Directors (CORD)/OTB osteoporosis curriculum. Discussion: The key findings were that institutions including OTB or any FLS in their programs had better availability of specialty consultants, faculty, and a FLS coordinator.